A randomised controlled cross-over double-blind pilot study protocol on THC:CBD oromucosal spray efficacy as an add-on therapy for post-stroke spasticity. Issue 9 (7th September 2017) - Marinelli, Lucio; Balestrino, Maurizio; Mori, Laura; Puce, Luca; Rosa, Gian Marco; Giorello, Laura; Currà, Antonio; Fattapposta, Francesco; Serrati, Carlo; Gandolfo, Carlo; Abbruzzese, Giovanni; Trompetto, Carlo
Abstract : Introduction: Stroke is the most disabling neurological disorder and often causes spasticity. Transmucosal cannabinoids (tetrahydrocannabinol and cannabidiol (THC:CBD), Sativex) is currently available to treat spasticity-associated symptoms in patients with multiple sclerosis. Cannabinoids are being considered useful also in the treatment of pain, nausea and epilepsy, but may bear and increased risk for cardiovascular events. Spasticity is often assessed with subjective and clinical rating scales, which are unable to measure the increased excitability of the monosynaptic reflex, considered the hallmark of spasticity. The neurophysiological assessment of the stretch reflex provides a precise and objective method to measure spasticity. We propose a novel study to understand if Sativex could be useful in reducing spasticity in stroke survivors and investigating tolerability and safety by accurate cardiovascular monitoring. Methods and analysis: We will recruit 50 patients with spasticity following stroke to take THC:CBD in a double-blind placebo-controlled cross-over study. Spasticity will be assessed with a numeric rating scale for spasticity, the modified Ashworth scale and with the electromyographical recording of the stretch reflex. The cardiovascular risk will be assessed prior to inclusion. Blood pressure, heart rate, number of daily spasms, bladder function, sleep disruption and adverse events will be monitored throughout the study. A mixed-model analysis of variance will be used to compare the stretch reflex amplitude between the time points; semiquantitative measures will be compared using the Mann-Whitney test (THC:CBD vs placebo) and Wilcoxon test (baseline vs treatment). Ethics and dissemination: The study was registered on the EudraCT database with number 2016-001034-10 and approved by both the Italian Medicines Agency (Agenzia Italiana del Farmaco) and local Ethics Committee 'Comitato Etico Regionale della Liguria'. Data will be made anonymous and uploaded to a open access repository. Results will be disseminated by presentations at national and international conferences and by publication in journals of clinical neuroscience and neurology.